Capital structure and taxation of companies operating within national and multinational corporate groups: evidence from the Visegrad Group of countries - Kluzek, Marta; Schmidt-Jessa, Katarzyna (Journal of Business Economics and Management, 2022)
The aim of this study is to review the level of debt and the impact of taxation on the capital structure of companies operating within national and multinational corporate groups in the countries of the Visegrad Group. In the research, financial data was used from 2012–2018 regarding entities forming part of corporate groups, and panel regression models with fixed effects were applied. According to the results of the research, domestic corporations are generally more leveraged and have a lower effective tax rate than multinational corporations. At the same time, the effective tax rate was significant only in six models out of sixteen, and mostly in the case of multinational corporations. The direction of impact was inhomogeneous. Other determinants of the financing structure which most often appeared as significant, in the case of companies operating both within domestic and international capital groups, include sales profitability as well as the tangibility and the age of the company. An additional analysis made for Poland and Slovakia determined that a change in the law on thin capitalization influenced entities’ capital structure determinants, but had no significant impact on the companies’ level of debt.First published online 25 February 2022